Revealing exciton masses and dielectric properties of monolayer semiconductors with high magnetic fields - Goryca, M.; Li, J.; Stier, A. V.; Taniguchi, T.; Watanabe, K.; Courtade, E.; Shree, S.; Robert, C.; Urbaszek, B.; Marie, X.; Crooker, S. A. (Nature communications, 2019)
In semiconductor physics, many essential optoelectronic material parameters can be experimentally revealed via optical spectroscopy in sufficiently large magnetic fields. For monolayer transition-metal dichalcogenide semiconductors, this field scale is substantial—tens of teslas or more—due to heavy carrier masses and huge exciton binding energies. Here we report absorption spectroscopy of monolayer MoS 2 , MoSe 2 , MoTe 2 , and WS 2 in very high magnetic fields to 91 T. We follow the diamagnetic shifts and valley Zeeman splittings of not only the exciton’s 1 s ground state but also its excited 2 s , 3 s , … , n s Rydberg states. This provides a direct experimental measure of the effective (reduced) exciton masses and dielectric properties. Exciton binding energies, exciton radii, and free-particle bandgaps are also determined. The measured exciton masses are heavier than theoretically predicted, especially for Mo-based monolayers. These results provide essential and quantitative parameters for the rational design of opto-electronic van der Waals heterostructures incorporating 2D semiconductors. The rational design of optoelectronic devices based on 2D materials relies on quantitative knowledge of their excitonic properties. Here the authors perform circularly-polarized absorption spectroscopy on monolayer MoS 2 , MoSe 2 , MoTe 2 and WS 2 in magnetic fields up to 91 T, and derive the effective exciton masses, binding energies, radii, dielectric properties, and free-particle bandgaps of these monolayer semiconductors